Modeling and experimental verification of thermally induced residual stress in RF-MEMS. (7th April 2015) - Somà, Aurelio; Saleem, Muhammad Mubasher
Abstract: Electrostatically actuated radio frequency microelectromechanical systems (RF-MEMS) generally consist of microcantilevers and clamped–clamped microbeams. The presence of residual stress in these microstructures affects the static and dynamic behavior of the device. In this study, nonlinear finite element method (FEM) modeling and the experimental validation of residual stress induced in the clamped–clamped microbeams and the symmetric toggle RF-MEMS switch (STS) is presented. The formation of residual stress due to plastic deformation during the thermal loading-unloading cycle in the plasma etching step of the microfabrication process is explained and modeled using the Bauschinger effect. The difference between the designed and the measured natural frequency and pull-in voltage values for the clamped–clamped microbeams is explained by the presence of the nonhomogenous tensile residual stress. For the STS switch specimens, three-dimensional (3D) FEM models are developed and the initial deflection at zero bias voltage, observed during the optical profile measurements, is explained by the residual stress developed during the plasma etching step. The simulated residual stress due to the plastic deformation is included in the STS models to obtain the switch pull-in voltage. At the end of the simulation process, a good correspondence is obtained between the FEM model results and the experimental measurements for both the clamped–clamped microbeams and the STS switch specimens.